Sustainable Production of Pulque and Maguey in Mexico: Current Situation and Perspectives - Valdivieso Solís, Dulce Gabriela; Vargas Escamilla, Carlota Amadea; Mondragón Contreras, Nayeli; Galván Valle, Gustavo Adolfo; Gilés-Gómez, Martha; Bolívar, Francisco; Escalante, Adelfo (Frontiers in Sustainable Food Systems, 2021)
Pulque is a traditional Mexican fermented, non-distilled alcoholic beverage produced by fermenting the fresh sap (aguamiel) extracted from several Agave (maguey) species cultivated for pulque production (mainly A. salmiana). This beverage was produced and consumed since Pre-Hispanic times by Mesoamerican civilizations, mainly in the Mexican Central Plateau, and is one of the essential alcoholic beverages produced and consumed during several centuries in Mexico. By 2019, annual pulque production was reported in 171,482 billion liters. Nevertheless, traditional pulque production faces several significant limitations, including the disappearance of large agave plantations and the extent of time required (at least 5 years) to complete the plant maturation for aguamiel extraction; traditional production practices; and the lack of an efficient stabilization process of the fermented product resulting in low shelf life. In opposition, successful examples of sustainable cultivation of maguey species for aguamiel extraction and the fermentation process's industrialization resulted in high-quality pulque production, with international exportation certification. In this contribution, we present a review of the most relevant aspects of the history and commercial relevance of pulque, the causes that resulted in its production debacle during the first half of the twentieth century, the current situation of its traditional production, and the successful efforts of industrial production of the beverage. We describe recent results on the analysis of the physicochemical characteristics of aguamiel and on the microbiology of the beverage explored by metagenomic techniques that can be proposed as a baseline to redefine the quality criteria of the beverage and to define for the first time a microbiological core to optimize its production. We describe the relevance of maguey species for aguamiel production as a fundamental element of agroforestry and the relevance of its sustainable production, in four sustainable plantation models to maintain a stable plant population to ensure the continuous extraction of aguamiel and pulque production. Finally, we describe some successful examples of beverage industrialization and potential applications of several microorganisms isolated from aguamiel, pulque, aguamiel concentrates, and the maguey to produce high-value bioactive products.